Prescribing patterns of antidiabetic drugs and glycaemic control in type 2 diabetes patients visiting tertiary care hospital based in Karachi, Pakistan - Jamali, Asifa; Ram, Nanik; Karim, Sehrish; Sattar, Saadia; Rashid, Malik S.; Islam, Najmul (International Journal Of Community Medicine And Public Health, 2023)
Background: Diabetes mellitus (DM) is a global health concern with elevated blood glucose levels and insulin dysfunction. Our study analyzed antidiabetic drug prescriptions and their effectiveness in managing type 2 diabetes (T2DM) with or without comorbidities. We aimed to gain insights into prescribing practices and efficacy in diverse patient populations. Methods: This retrospective study was conducted at The Aga Khan University in Karachi, Pakistan, over a three-month period. It analysed prescriptions of anti-diabetic drugs for male and female patients aged 18 years and above with type 2 diabetes mellitus. Patient data, including prescribed drugs, diabetes duration, co-morbid conditions, and HbA1c levels, were reviewed using the hospital’s Health Information Management System (HIMS). Results: Data from 552 diabetic patients were analysed. The mean age of participants with type-2 DM was 58 years, with 53.3% males and 46.7% females. 25.2% had diabetes for 5-10 years. Good glycaemic control was achieved by 48.7% of patients. Metformin (83.9%), dipeptidyl peptidase 4 inhibitors (DPP4) inhibitors (61.1%), and sodium-glucose transport 2 inhibitors (SGLT2) inhibitors (54.0%) were the most prescribed medications. Three-drug combinations were predominant (41.5%). Conclusions: Metformin was the most prescribed monotherapy for T2DM, followed by DPP4 inhibitors and SGLT2 inhibitors. Common combinations included DPP4 inhibitors with metformin, three-drug combinations with metformin, DPP4 inhibitors, and SGLT2 inhibitors, and four-drug combinations with metformin, DPP4 inhibitors, SGLT2 inhibitors, and sulfonylurea. DPP4 inhibitors were commonly used after metformin due to availability and cost-effectiveness. Glucagon-like peptide-1 inhibitors (GLP-1) analogs were less commonly prescribed due to cost, patient preference, and concerns about side effects.